Reproductive biology and recruitment of Xiphopenaeus kroyeri in a marine protected area in the Western Atlantic: implications for resource management - Almeida, Ariadine C. [UNESP]; Antonio Baeza, J.; Fransozo, Vivian [UNESP]; Castilho, Antonio L. [UNESP]; Fransozo, Adilson [UNESP] (Inter-research, 2012)
The potential of a recently established marine protected area (MPA) in the Western Atlantic, Brazil, as a 'seed production' and nursery ground for Xiphopenaeus kroyeri, an intensively exploited penaeid shrimp, was investigated in an attempt to reveal any future benefit of this new MPA to adjacent populations experiencing heavy exploitation. Overall, we observed that males and females >12 and 20 mm carapace length, respectively, contributed the most to reproduction in the studied population. Reproductive activity of X. kroyeri was continuous at the MPA; 2 annual reproductive peaks were recorded from March to April and from November to December, which were followed by recruitment events occurring from March to April 2009 and November 2009. Sediment, temperature, and algae and plant biomass floating near the bottom were relevant in driving reproductive activity and recruitment in X. kroyeri. The high reproductive potential of the studied population and the occurrence of abundant juveniles throughout the sampling area, indicating the existence of a nursery ground within the region, suggest that this MPA might provide important benefits in the near future. We argue in favor of future long-term studies on the larval dispersion, reproductive biology and ecology of X. kroyeri in MPAs and non-MPAs to construct a base for future management of this species and to aid stock recovery in fishing areas that are heavily exploited.
Keywords: Marine protected area; Xiphopenaeus kroyeri; Size at first maturity; Reproductive potential; Nursery ground; Environmental parameters; Stock recovery